Project-Based Learning-Based Scramble Text Media to Improve Learning Outcomes in Writing Romantic Poetry - Febry Marindra Cysbya Erdlanda; Tita Rosmiati (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe the improvement of students’ abilities in writing romantic poetry and students’ responses to learning to write romantic poetry.. The research was conducted at SMA Negeri 1 Cianjur in April 2025. The class X students who were used as the research population were 434 students with a research sample of 35 students. Experimental methodone group pretest posttest designwith the data collection technique used is a test technique in the form of a test sheet and a non-test technique in the form of a questionnaire sheet. The data analysis tool used is the use of the SPSS application to process test result data and matrix tabulation to present student response questionnaire data. The findings obtained that the average class value in the pretest was 73 with a Classical Absorption Capacity (DSK) of 60% with a sufficient increase category while the average class value in the posttest was 96 with a DSK of 94% with a very good increase category. In this study, a Wilcoxon hypothesis test was carried out because the sample data was not normally distributed with the results of the hypothesis test obtained an Asymp.Sig value (2-tailed) of 0.000 <0.05, then H0 was rejected, H1 was accepted which means that learning usingscramble textPjBL-based learning can improve students’ ability in writing romantic poetry with the results of the N-Gain test obtaining an average score of 0.8805 in the high category with a percentage of 88% in the effective category, which means that the mediascramble textThe PjBL model is effectively used in learning to write romantic poetry. The overall student response, both to the media and the learning model used, showed a positive response, meaning that students liked, enjoyed, and found it easy for them to create/write romantic poetry.